1977
DOI: 10.1111/j.1746-1561.1977.tb01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Health Office Visits in an Urban School District

Abstract: A survey of 3,048 school clinic visits (a 5% random sample by school of all visits during one school year) revealed the most frequent complaints or reasons for visits of school children in grades kindergarten through twelve. Minor trauma was the complaint identified in the largest proportion of clinic visits at all levels. Taking prescribed medication was the second most frequent reason for clinic visits at the elementary level. Headache was a frequent complaint presented in high school clinic visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In line with other international reports, headaches were regarded as one of the most common reasons for students seeking help at the school nurses' office (6,7,13,14,17). However, the stated reasons for adolescents seeking help when presenting with headaches at the school health care have been questioned in that many of the students only want to rest and do not seek help specifically for their headaches complaints (13).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In line with other international reports, headaches were regarded as one of the most common reasons for students seeking help at the school nurses' office (6,7,13,14,17). However, the stated reasons for adolescents seeking help when presenting with headaches at the school health care have been questioned in that many of the students only want to rest and do not seek help specifically for their headaches complaints (13).…”
Section: Discussionsupporting
confidence: 68%
“…In epidemiological studies, recurrent headaches have been found to be one of the most common health and pain complaints reported by school children and adolescents (1–5). Headaches are also one of the most common health problems among school children encountered in school health services, besides minor trauma and infections (6, 7). Although headache is a common health problem, school health personal see headaches in school children as causing only a slight disruption of their school functioning (8, 9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…71, No. 4 needed to effect a general reorientation away from the natural tendencies among all health personnel to interact with clients in ways which tend to foster dependence upon the system. However, if such efforts could be concentrated on the school health service, then schools could become places where children could practice the skill of appropriate use of health services long before their misuse of them has major economic implications, either for themselves or for society.…”
Section: Discussionmentioning
confidence: 99%